2022
DOI: 10.1038/s41396-022-01295-8
|View full text |Cite
|
Sign up to set email alerts
|

Metaproteome plasticity sheds light on the ecology of the rumen microbiome and its connection to host traits

Abstract: The arsenal of genes that microbes express reflect the way in which they sense their environment. We have previously reported that the rumen microbiome composition and its coding capacity are different in animals having distinct feed efficiency states, even when fed an identical diet. Here, we reveal that many microbial populations belonging to the bacteria and archaea domains show divergent proteome production in function of the feed efficiency state. Thus, proteomic data serve as a strong indicator of host f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 60 publications
(77 reference statements)
1
4
0
Order By: Relevance
“…Previous studies reported controversial effects of urea supplementation on gas production and dry matter digestibility ( Salem et al, 2013 ; Spanghero et al, 2018 ; Muthia et al, 2021 ; Kour et al, 2023 ), and we detected that bacterial counts decreased but gas production and dry matter digestibility were stable over a 23-day continuous batch culture of rumen microbiota under high urea condition. The theory of functional redundancy in rumen microbiota might support these observations ( Wemheuer et al, 2020 ; Sasson et al, 2022 ), and we inferred that functional redundant microbes might be partially removed, while core bacteria associated with dry matter digestion might be preserved after 23 days of continuous batch culture.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies reported controversial effects of urea supplementation on gas production and dry matter digestibility ( Salem et al, 2013 ; Spanghero et al, 2018 ; Muthia et al, 2021 ; Kour et al, 2023 ), and we detected that bacterial counts decreased but gas production and dry matter digestibility were stable over a 23-day continuous batch culture of rumen microbiota under high urea condition. The theory of functional redundancy in rumen microbiota might support these observations ( Wemheuer et al, 2020 ; Sasson et al, 2022 ), and we inferred that functional redundant microbes might be partially removed, while core bacteria associated with dry matter digestion might be preserved after 23 days of continuous batch culture.…”
Section: Discussionsupporting
confidence: 56%
“…The authors concluded that highly efficient animals process a less diverse array of metabolites and specialize in the production of fatty acids with a concomitant reduction in methane production [ 106 ]. Further results published by the same group revealed that proteomics data are more informative to delineate the actual microbiome metabolic profile than metagenomics data, thus fueling a long-standing debate concerning the intrinsic divergence between gene content and actual protein expression in metagenomics studies [ 114 ]. Nevertheless, these and a myriad of additional studies led to the proposal of a host genetics-microbiome axis as the master control mechanism of metabolism in ruminants [ 103 , 115 ].…”
Section: Role Of Prevotella In Lignocellulose Proc...mentioning
confidence: 99%
“…Additionally, this method enables the detection of post-translational modifications. Metaproteomic analysis can be approached through targeted or untargeted strategies (Sasson et al 2022 ).…”
Section: Approaches For Microbiological Research For the Study Of Mic...mentioning
confidence: 99%
“…Such data can then be interpreted in the context of the milieu of interactions in microbial communities and host and environmental interfaces (Gloag et al 2013 , Regmi et al 2022 ). For example, Sasson et al ( 2022 ) demonstrated the increased depth of insight possible with metaproteomic data paired with metagenomic data in the rumen microbiome. Their study revealed associations between protein production profiles of specific metagenome-assembled genomes (in addition to phyla) and cattle feed efficiency phenotypes.…”
Section: Approaches For Microbiological Research For the Study Of Mic...mentioning
confidence: 99%